Climate change impact on coastal communities in Malaysia - Abas, Norzaida; Mohd Daud, Zalina; Mohamed, Norazizi; Abdul Halim, Syafrina (Penerbit Akademia Baru, 2017)
Climate change is undeniably the greatest issue facing our society. Around the globe, increasingly unpredictable weather patterns and extreme weather events are observed, causing considerable risks to human lives, properties and health safety and also on the natural ecosystem. The magnitude and impacts of climate change are growing, and particularly in Malaysia, studies show increases in temperature and changes in rainfall regimes. Such changes have profound implications, especially for coastal communities. Since knowledge and perceptions of the public on climate change could affect the success of implemented adaptation and mitigation options, it is essential to conduct assessments to gather such information. A public awareness and perception study was conducted at Sabak and Tanjung Karang, two coastal communities which were affected by changes in sea level and flooding incidences. The knowledge level and perceptions of climate change among respondents were assessed covering areas such as level of awareness of the respondents, their perceptions of climate change issues, their sentiments on climate change and adaptation measures, their socioeconomic activity and the effect on their lives. Results show that majority of respondents were aware of climate change issues and challenges. High levels of concern about climate change were expressed with the majority were worried and uncertain about the climate change impact and hoped for government measures. Almost half of respondents cited significant damage to their properties and reduction in income generation. Overall, the results of the present study gave insights of the affected parties on perceptions and awareness pertaining to climate change, which could potentially be used to promote greater awareness of climate change matters and to gauge the public response to related policies and strategies.